RISK-BASED APPROACH IN LABOR AUDIT AND COSO INTERNAL CONTROL MODEL - Nomozov Ilhomjon Ziyadullah ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the issues of risk-based approach and COSO internal control model in payroll audit. The 3-component model of audit risk (AR = IR × CR × DR) is analyzed. 7 main risks encountered in payroll audit are classified: fake employees, manipulation of working hours, incorrect calculation of bonuses, incorrect withholding of taxes, delay in social payments, manipulation of electronic systems, falsification of documents. An assessment methodology is developed based on the 5 components of the COSO internal control model.